Investigating the impacts of a recirculation sedimentation application on microalgae biomass cultivation in wastewater treatment - Bostanci, Ismail S.; Koca Akkaya, Ebru (TAYLOR & FRANCIS INC, 2025)
Commercial microalgae production is often interrupted by contamination, leading to short production cycles, reinoculation needs, and culture collapses, significantly increasing costs. This study focuses on investigating Recirculated Sedimentation Application (RSA) to control contamination in microalgae culture systems used for wastewater treatment. Chlorella vulgaris culture was grown in an unsterilized mixture of tertiary treatment effluent and centrate of anaerobic digestion wastewater sludge over a 90-day experimental period. 60 L raceway reactor was operated under a light intensity of 275 mu M m(-2).s(-1) with a 16:8 h light-dark photoperiod. To evaluate the effect of RSA on biological-based problems, the experiment was conducted in three phases. The benefits of utilizing RSA were established through the following observations: effective removal of contaminants at an acceptable level without releasing the culture; extension of the biofilm formation time on the inner walls; inhibition of heterotrophic bacteria and nitrification; enhancement of the suspended solids retention capacity of the raceway tank (up to 770 mg.L-1); and improvement in ammonium removal rate to approximately 30 mg.L(-1)d(-1). The ideal salinity level for both ammonium removal and biomass concentration in RSA should be below 0.02%. These findings demonstrate the potential of phycoremediation for sustainable wastewater treatment and contribute to environmental bioremediation strategies.
Keywords: Biomass; culture collapse; reactor contamination; sustainable microalgae production; wastewater treatment; PHOSPHORUS; GROWTH; CHLORELLA; AMMONIUM; NITROGEN; CULTURE; REMOVAL; ALGAE; Environmental Sciences & Ecology